The Impact of Crisis Intervention Team Response, Dispatch Coding, and Location on the Outcomes of Police Encounters with Individuals with Mental Illnesses in Chicago. (28th February 2021) - Watson, Amy C; Owens, Linda K; Wood, Jennifer; Compton, Michael T
Abstract: The Crisis Intervention Team (CIT) model has been implemented in over 3, 000 communities across the USA. Research to date has shown beneficial results in terms of officers' knowledge, attitudes, self-efficacy, stigma, and force preferences. This study aimed to broaden the lens on the implementation context of CIT to examine whether factors in the environment and response process affect how calls are resolved. This study focused on several factors—CIT response, call location, and upstream decisions to pre-identify calls as mental health-related—that may impact call outcomes. Our findings suggest that CIT response, dispatch coding, and the places where calls originate play a role in shaping outcomes. More research is needed to unpack the effects of this wider CIT implementation environment.